1988
DOI: 10.1007/bf01849267
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pregnancy with an IUDin situ — a population based case — control study

Abstract: Use of IUDs was examined among 962 women whose pregnancy was terminated at the University Hospital of Trondheim, Norway during 1983. Ectopic pregnancy was significantly more often diagnosed among women with an IUD in place at conception compared to non-users (7.8% vs 1.3%, p less than 0.01). Despite removal of the IUD during the first trimester, women who became pregnant with an IUD in situ had spontaneous abortion more often than non-users (15.6% vs 7.0%, p less than 0.05). The causal significance of these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
2
7
1
Order By: Relevance
“…Several studies have reported a higher rate of miscarriage in women who conceive an intrauterine pregnancy despite the presence of an IUD [18, 48, 52]. Moreover, the present study showed a higher rate of fetal death.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Several studies have reported a higher rate of miscarriage in women who conceive an intrauterine pregnancy despite the presence of an IUD [18, 48, 52]. Moreover, the present study showed a higher rate of fetal death.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have established a higher risk of complications, such as miscarriage and sepsis, in pregnancies with a retained IUD than in those with early IUD removal [2, 18, 48, 52]. For this reason, the U.S. Food and Drug Administration (FDA) recommends that IUDs whose tails are visible be removed in early pregnancy [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that pregnancies with retained IUD had a higher rate of complications, such as miscarriage, PROM, preterm birth, C-section, and shorter gestational age at delivery in comparison to pregnancies with removed IUD. This was consistent with previous studies [11][12][13][14]. A higher proportion of neonates born to mothers with retained IUD were admitted to NICU than that of those removed IUD, but this was not statistically significant.…”
Section: Discussionsupporting
confidence: 94%
“…Most reports about complications date from the 1970s and 1980s, and suggest an increased risk of miscarriage, with a higher loss rate if a copper IUD is retained (62,63) than if it is removed (64). Most reports about complications date from the 1970s and 1980s, and suggest an increased risk of miscarriage, with a higher loss rate if a copper IUD is retained (62,63) than if it is removed (64).…”
Section: In Pregnant Women Does Removal Of the Iud Affect Pregnancy mentioning
confidence: 99%